Psychosocial Interventions for Health and Well-Being (Springer India, 2018)
This volume provides multifaceted and multidisciplinary insights into the growing field of health studies. Providing inputs from the behavioural sciences as well as social sciences, it discusses the issues of recovery from illness, and growth and wellbeing, as situated in social and eco-cultural contexts, and addresses the modalities of health-related interventions in diverse contexts. The specific themes taken up by the contributors are post-trauma growth, resilience, gender and health, distress and wellness, indigenous healing, counselling and psychotherapy, disability-related interventions, self-healing, as well as health issues of special groups like adolescents and the elderly, cancer patients and those suffering from other chronic illnesses. Till recently, the medical model has prevailed as the chief form of understanding health and illness. This has led to marginalization of the context, localization of all health and wellness components within the individual, and to biological reductionism. The contributions to this volume propose corrective measures and provide diverse approaches in a balanced manner. This volume is useful for researchers and practitioners interested in health studies, including the behavioural sciences, social work, medical anthropology, and public health.